2014
DOI: 10.1186/1471-244x-14-67
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of integrated treatment in patients with substance use disorders co-occurring with anxiety and/or depression - a group randomized trial

Abstract: BackgroundIntegrated Treatment (IT) has proved effective in treating patients with Substance Use Disorders (SUD) co-occurring with severe Mental Disorders (MD), less is known about the effectiveness of IT for patients with SUD co-occurring with less severe MD.The aim of this study was to investigate the effectiveness of IT for patients with SUD co-occurring with anxiety and/or depression on the following parameters:1. The use of substances, as measured by the Alcohol Use Identification Test (AUDIT), the Drug U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 63 publications
(56 reference statements)
2
22
0
Order By: Relevance
“…Numerous studies have indicated a high degree of comorbidity between major depression and substance use disorders. This comorbidity is associated with a poorer effect of treatment, resulting in poorer psychosocial functioning, a higher number of days in treatment, higher attrition rates, more admissions, and a higher burden of disease arising from both major depression and substance use disorder 26. This study found a relationship between depression and problem recognition, and this finding is in accordance with a previous report 27.…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies have indicated a high degree of comorbidity between major depression and substance use disorders. This comorbidity is associated with a poorer effect of treatment, resulting in poorer psychosocial functioning, a higher number of days in treatment, higher attrition rates, more admissions, and a higher burden of disease arising from both major depression and substance use disorder 26. This study found a relationship between depression and problem recognition, and this finding is in accordance with a previous report 27.…”
Section: Discussionsupporting
confidence: 91%
“…As this presents a common and often underestimated comorbidity [63, 64], future studies should assess and control for depression when comparing patients with OD and healthy controls. Especially in severe substance use disorders, other psychopathological impairments are also common and barely improve during maintenance therapy [65-68]. However, in our regression model, the score of the SCL-90R was no longer significant after controlling for other confounders.…”
Section: Discussionmentioning
confidence: 42%
“…A smaller (N ¼ 55) but randomized Norwegian study recently showed that integrated treatment in patients with substance use disorders co-occurring with anxiety and/or depression compared to treatment as usual increased motivation for substance use treatment after 12 months significantly in the intervention group, while substance use was decreased in both groups (Wüsthoff et al 2014). In the intervention group, therapists were trained in motivational interviewing and CBT.…”
Section: Prevention and Therapymentioning
confidence: 96%